2015
DOI: 10.1016/j.jaap.2014.11.022
|View full text |Cite
|
Sign up to set email alerts
|

Production and characterization of a new quality pyrolysis oil, char and syngas from digestate – Introducing the thermo-catalytic reforming process

Abstract: Where a licence is displayed above, please note the terms and conditions of the licence govern your use of this document. When citing, please reference the published version. Take down policy While the University of Birmingham exercises care and attention in making items available there are rare occasions when an item has been uploaded in error or has been deemed to be commercially or otherwise sensitive.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
64
1
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 120 publications
(84 citation statements)
references
References 8 publications
5
64
1
1
Order By: Relevance
“…The digestate sample showed a liquid composition and liquid yield in accordance with that obtained by Neumann and coworkers [25] processing the same feedstock on a 2 kg/h laboratory scale thermo-catalytic reforming (TCR®) reactor [30].…”
Section: Biomasssupporting
confidence: 78%
See 1 more Smart Citation
“…The digestate sample showed a liquid composition and liquid yield in accordance with that obtained by Neumann and coworkers [25] processing the same feedstock on a 2 kg/h laboratory scale thermo-catalytic reforming (TCR®) reactor [30].…”
Section: Biomasssupporting
confidence: 78%
“…A pelletized solid digestate deriving from an anaerobic digestion plant operated by Neue Energie Steinfurt GmbH, Germany (NESt) using a mixture of maize silage (62%), cattle slurry (17%), pig slurry (17%) and cereals (4%) was used as a feedstock [25].…”
Section: Feedstockmentioning
confidence: 99%
“…Pedrazzi et al (2015) have shown that ashes create agglomerates, which obstruct the brazier holes and partially choke the combustion after few minutes 107 . Pyrolysis process is another promising technology that can make use of solid digestate 119,122 . Pyrolysis is an endothermic thermochemical process which can recover energy from organics, regardless whether the organic matter is biodegradable or not 123 .…”
Section: Bioethanol Productionmentioning
confidence: 99%
“…Apart from contributing to carbon immobilization and higher nutrient stability, the pyrolysis of RBP to produce biochar can also allow us to recover energy in a double way in the form of biogas and biofuel at different stages of waste material processing. Therefore, the production of RBPderived biochar is an interesting solution, which may lead to carbon material with better properties than the feedstocks and it also may be useful as an addition to soils [10,11].…”
Section: Introductionmentioning
confidence: 99%